Association of IFN-γ +874 A/T SNP and hypermethylation of the -53 CpG site with tuberculosis susceptibility - Álvarez, Guadalupe Inés; Hernández Del Pino, Rodrigo Emanuel; Barbero, Angela María; Estermann, Martín Andrés; Celano, Josefina; Musella, Rosa María; Palmero, Domingo Juan; García, Verónica Edith; Pasquinelli, Virginia (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Tuberculosis (TB) is now the 2nd leading infectious killer after COVID-19 and the 13th leading cause of death worldwide. Moreover, TB is a lethal combination for HIV-patients. Th1 responses and particularly IFN-γ are crucial for immune protection against Mycobacterium tuberculosis infection. Many gene variants for IFNG that confer susceptibility to TB have been described in multiple ethnic populations. Likewise, some epigenetic modifications have been evaluated, being CpG methylation the major epigenetic mark that makes chromatin inaccessible to transcription factors, thus avoiding the initiation of IFNG transcription. Methods We evaluated both genetic and epigenetic changes involved in IFN-γ production and TB susceptibility in Argentine population. Amplification refractory mutation system-polymerase chain reaction (ARMS-PCR) was performed for the IFN-γ +874 A/T polymorphism (rs2430561) genotyping in 199 healthy donors (HD) and 173 tuberculosis (TB) patients. IFN-γ levels from M. tuberculosis-stimulated PBMCs were measured by ELISA. The methylation status at the -53 CpG site of the IFNG promoter in individuals with latent infection (LTBI), TB and HD was determine by pyrosequencing. Results Using a case-control study, we found that A allele and, consequently, AA genotype were overrepresented in patients with active disease. Moreover, HD carrying T allele (AT or TT genotype) evidenced an augmented IFN-γ secretion compared to TB patients. Codominance was the genetic model that best fits our results according to the Akaike information criterion (AIC). In addition, increased methylation levels at the -53 CpG site in the IFN-γ promoter were observed in whole blood of patients with active TB compared to LTBI individuals. Discussion IFN-γ is regulated by genetic variants and epigenetic modifications during TB. Besides, AA genotype of the rs2430561 single nucleotide polymorphism could be considered as a potential TB susceptibility genetic biomarker in Argentina and the methylation of the -53 CpG site could result in a useful predictor of TB reactivation.